ANGGARAN BIAYA TENAGA KERJA SEBAGAI ALAT PERENCANAAN DAN PENGENDALIAN BIAYA PERUSAHAAN - Muammar Khadafi; Cut Putri; Nayla Hafizah; Ratih Ananda; Kasna Irma Daleni; Duta Abi Nuh (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
Labor cost budgeting is one of the important components in a company's budgeting system because labor costs have a large proportion in the operational cost structure, especially in manufacturing companies. This study aims to analyze the role of the labor cost budget as a tool for planning and controlling company costs. The research method used is a qualitative descriptive method with a literature study approach, which examines various theories and concepts related to the labor cost budget. The results of the discussion show that the labor cost budget functions as a guideline in determining labor needs, controlling expenses, increasing efficiency, and being the basis for calculating the cost of production. With systematic and realistic budgeting, companies can optimize labor usage and minimize the risk of wasted costs.